2015
DOI: 10.1016/j.joca.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four chondral repair techniques in the hip joint: a biomechanical study using a physiological human cadaveric model

Abstract: Fibrin glue on its own does not provide sufficient fixation to repair chondral flaps on the acetabular surface. Cyanoacrylate repairs universally failed midway through the testing protocol employed here, raising doubts as to the effectiveness of that technique. The suture and hydrogel scaffold technique were the most reliable for chondral repair at any given cycle. The results of this biomechanical study demonstrate the relative effectiveness of chondral repair and fixation techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…24,25 However, biomechanical testing has shown that gluing on its own provides insufficient fixation of the chondral flaps. 26 A more physiological clot produced by subchondral drilling might sufficiently stabilse the cartilage Table 1. Demographic data of the study and the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 However, biomechanical testing has shown that gluing on its own provides insufficient fixation of the chondral flaps. 26 A more physiological clot produced by subchondral drilling might sufficiently stabilse the cartilage Table 1. Demographic data of the study and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 However, biomechanical testing has shown that gluing on its own provides insufficient fixation of the chondral flaps. 26 A more physiological clot produced by subchondral drilling might sufficiently stabilse the cartilage flap. Second, previous studies found evidence that even though the chondral flaps appear normal macroscopically, the biochemical properties and percentage of live chondrocytes are significantly reduced and variable stages of matrix and chondrocyte damage are present.…”
Section: Discussionmentioning
confidence: 99%
“…Cassar-Gheiti et al [76] compared four chondral repair techniques in a cadaver model. The authors created chondral flaps in 24 cadavers, treating six hips each with either fibrin glue, cyanoacrylate, a suture technique or an agarose hydrogel scaffold sealed with fibrin glue.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Biomechanical data published on chondral repair techniques has shown improve resistance to shear forces across the chondral surface when compared to fibrin adhesive repair in cadaveric models [109]. Furthermore we have identified early biomechanical failure in fibrin adhesive repair, which failed at only 50 cycles, while suture of chondral flaps were more biomechanically stable throughout the 1500 cycle testing [109]. The small number of reported outcomes and early laboratory failure may limit fibrin glue clinical use, however, both fibrin glue, suture and cyanoacrylate repair warrant further investigation.…”
Section: Cyanoacrylatementioning
confidence: 99%